Religion and the gender vote gap: women's changed political preferences from the 1970s to 2010 - Manow, Philip; Emmenegger, Patrick (2012)
Abstract: "For many years women tended to vote more conservative than men (the ‘old’ gender vote gap), but since the 1980s this gap in many countries has shifted direction: now women in many countries are more likely to support left parties than men of the same age, in the same income bracket, and at the same educational level (the ‘new’ gender vote gap). The literature largely agrees on a set of political-economic factors explaining the change in women’s political orientation: changed employment patterns, women’s higher educational achievements, and higher divorce rates. These trends turned women into supporters of generous social programs that promise to ‘de-familialize’ services formerly provided privately within the family. In this paper, we demonstrate that these conventional political-economic factors fall short in explaining the old gender vote gap. We may therefore also harbor doubts whether they provide us with a full story for the new gender vote gap. Instead, we highlight the impo